Предмет: Математика, автор: алина1701

-3 3/5+(-2 1/3)+4 8/15-1 5/6-(-6 7/10)+1/2

Ответы

Автор ответа: Ewwas
0

-3 3/5+(-2 1/3)+4 8/15-1 5/6-(-6 7/10)+1/2= -18/5 -7/3+68/15- 11/6 + 67/10+ 1/2 = (-18*12 -7*20+ 68*4 - 11*10 +67*6 +60) /60 = (-216-140+272-110+402+60)/60 = 268/60= 67/15 = 4  7/15

 

 

Автор ответа: Svet1ana
0

-3frac{3}{5}+(-2frac{1}{3})+4frac{8}{15}-1frac{5}{6}-(-6frac{7}{10})+frac{1}{2}=4frac{1}{6}

 

1) -3frac{3}{5}+(-2frac{1}{3})=-3frac{3}{5}-2frac{1}{3}=-(3frac{3}{5}+2frac{1}{3})=-(frac{18}{5}+frac{7}{3})=-(frac{51+35}{15})=-frac{86}{15}=-5frac{11}{15}

 

2) -5frac{11}{15}+4frac{8}{15}=-frac{86}{15}+frac{68}{15}=frac{68}{15}-frac{86}{15}=frac{68-86}{15}=-frac{18}{15}=-frac{6}{5}=-1frac{1}{5}

 

3) -1frac{1}{5}-1frac{5}{6}=-frac{6}{5}-frac{11}{6}=-(frac{6}{5}+frac{11}{6})=-(frac{36+55}{30})=-frac{91}{30}=-3frac{1}{30}

 

4) -3frac{1}{30}-(-6frac{7}{10})=-3frac{1}{30}+6frac{7}{10}=-frac{91}{30}+frac{67}{10}= frac{67}{10}-frac{91}{30}=frac{201-91}{30}=frac{110}{30}=frac{11}{3}=3frac{2}{3}

 

5) 3frac{2}{3}+frac{1}{2}=frac{11}{3}+frac{1}{2}=frac{22+3}{6}=frac{25}{6}=4frac{1}{6}

Похожие вопросы
Предмет: Қазақ тiлi, автор: kudasbaevnurlan